Comparative Morphological Study of Feathers of Broiler and Layer Chicken - Sayali Chitnis; S. A. Gaikwad; S. B. Lambate; S.D. Ingole; R.J. Zende (Indian Journal of Veterinary Anatomy, 2024)
Chicken feathers are essential components of avian anatomy, which plays a crucial role in various physiological functions, including flight, thermoregulation, and display. This study focused on the morphological examination of chicken feathers to unravel the intricate structures that contribute to their diverse functionalities. Microscopic analyses revealed the hierarchical organization of feathers, the arrangement of barbs, barbules, and hooklets that create the characteristic vane structure. The intricate design of feathers not only facilitates flight but also contributes to the thermal insulation of birds in various environmental conditions. Understanding the morphological variations in feathers of different body regions contributes to insights into their specialized functions, such as contour feathers for aerodynamics, down feathers for insulation, and ornamental feathers for social signaling.